Organic colonic lesions in patients with irritable bowel syndrome: A comparative study - F. Ejtehadi; M.H. Anbardar; M.H. Imanieh; R. Niknam; G.R. Sivandzadeh (Revista de Gastroenterología de México (English Edition), 2023)
Introduction and aims: Any alarm symptoms in patients with irritable bowel syndrome (IBS) should be carefully evaluated. Colonoscopy is a standard diagnostic procedure for evaluating the colonic mucosa and ruling out probable diseases responsible for patient symptoms. We analyzed the colonoscopy findings in patients with and without IBS. Material and methods: Ninety-six patients with IBS and 101 without IBS were consecutively enrolled in the study. All the patients in the IBS group met the Rome IV criteria, and underwent colonoscopy due to the appearance of red flags. The colonoscopy findings were compared between the 2 groups of patients. Results: The main indications for colonoscopy in the IBS group were progressive abdominal pain (36.7%), rectal bleeding with fresh blood (17.7%), and occult blood in stool (12.5%). In the non-IBS group, the most prevalent indicators were rectal bleeding with fresh blood (37.6%), colorectal cancer surveillance (21.8%), and abdominal pain (13.9%). The most common macroscopic findings in the 2 groups were hemorrhoids, polyps, and anal fissure. There were no statistically significant differences with respect to the microscopic and macroscopic findings between groups. Conclusions: We concluded that the prevalence of organic lesions in the colon of patients with IBS was the same as that in the patients without IBS. The Rome IV criteria accurately predicted IBS. Additional evaluation through colonoscopy in IBS should be based on the presence of alarm features. Resumen: Introducción y objetivos: Cualquier síntoma alarmante debe evaluarse cuidadosamente en los pacientes con síndrome del intestino irritable (SII). La colonoscopia es un procedimiento de diagnóstico estándar para evaluar la mucosa del colon y descartar probables enfermedades responsables de los síntomas de los pacientes. Analizamos los hallazgos colonoscópicos en pacientes con SII y pacientes sin SII. Material y métodos: Noventa y seis pacientes con SII y 101 sin SII fueron registrados en el estudio de forma consecutiva. Todos los pacientes del grupo con SII cumplieron los criterios de Roma IV y se sometieron a una colonoscopia debido a la aparición de signos alarmantes. Los hallazgos de la colonoscopia se compararon entre los grupos de pacientes. Resultados: Los principales indicadores para colonoscopia en el grupo con SII fueron dolor abdominal progresivo (36.7%), sangrado rectal fresco (17.7%) y sangre oculta en heces (12.5%). En el grupo sin SII, los indicadores de mayor prevalencia fueron sangrado rectal fresco (37.6%), vigilancia del cáncer colorrectal (21.8%) y dolor abdominal (13.9%). En ambos grupos, los hallazgos macroscópicos más comunes fueron hemorroides, pólipos y fisura anal. No hubo diferencias estadísticamente significativas entre los grupos en los hallazgos macroscópicos y microscópicos. Conclusiones: Concluimos que la prevalencia de lesiones orgánicas en el colon de pacientes con SII es la misma que en pacientes sin SII. Los criterios de Roma IV predijeron el SII con precisión. La evaluación colonoscópica adicional en el SII debe basarse en la presencia de signos de alarma.